Time to tap Africa's livestock genomes - Hanotte, Olivier H.; Dessie, Tadelle; Kemp, Stephen J. (American Association for the Advancement of Science, 2010)
We need to better understand and exploit the genetic diversity of Africa's indigenous livestock breeds—before they fade away.